Pengembangan Kemampuan Eksplorasi Anak Usia 5-6 Tahun melalui Kegiatan Bermain Plastisin di TKN Pembina Syamtalira Bayu - Fuadi, Noval (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2021)
The purpose of applying the plasticine playing method is expected to be able to develop the fine motor skills of children aged 5-6 years so that they are able to draw according to their ideas, imitate shapes, use stationery correctly, cut according to patterns, paste pictures correctly, express themselves through detailed drawing movements and perform exploration with various media and activities. Qualitative research approach with the type of classroom action research. Sources of data in this study were children in the B3 group at Pembina Syamtalira Bayu TKN which consisted of 18 children and one teacher in the B3 group at Pembina Syamtalira Bayu TKN. Data collection techniques used are observation, documentation, and interviews. Data analysis techniques are data reduction, describing data, and making conclusions. The results obtained are: 1) through initial observations, it 6was found that 12 children had not been able to arrange blocks as expected and only 6 children were able to arrange blocks into building shapes like those made by the teacher and could make various other buildings themselves so that it can be concluded that children's exploration abilities undeveloped. 2) After taking action in cycle 1, the condition of children's exploration abilities changed for the better with details: (a) 0% developed very well, (b) 16.67% developed as expected, (c) 15% began to develop, and (d) 0% undeveloped. 3) Based on the results in the second cycle, the results obtained are: (a) 94.44% of children's ability levels are very well developed, (b) 5.6% are developing as expected, (c) 0% are starting to develop, and (d) 0% are not yet developed. The success rate of children's exploration abilities can be said to be successful very good predicates. Besides being able to develop fine motor skills for children, the application of the play method can also develop children's logical thinking skills in recognizing shapes, sizes, or colors in the process of forming plasticine. In addition, teachers.